The inner image: an examination of the life of Helen Elizabeth Martins leading to her creation The Owl House and A Camel Yard as outsider art - Ross, Susan Imrie (Rhodes University, Faculty of Humanities, Department of Fine Art, 1996)
The Owl House is situated in the Karoo village of Nieu Bethesda, and the person responsible for its creation, Helen Elizabeth Martins (1897-1976), is South Africa's best known Outsider artist. A number of newspaper and magazine articles, television programmes, radio interviews, play, films, short stories, theses and art works have resulted directly from her work. Interest in The Owl House continues to grow, with visitors coming from all over South Africa, and various parts of the world,to visit it. The Owl House was Helen Martins' home for most of her 78 years. During the last 30 or so years of her life she devoted all her time and energy to transforming the interior of her house into a glistening fantasy world of colour and light, using crushed glass stuck to almost every surface, coloured glass pane inserts in the walls, mirrors of many sizes and shapes, and countless paraffin lamps and candles. She called her garden' A Camel Yard', and filled it with over 500 cement statues, structures and bas reliefs. All the labour involved, apart from crushing and sorting the coloured glass, was provided by at least four different men, who assisted her over the years, Johannes Hattingh, Jonas Adams, Piet van der Merwe and Koos Malgas, though Helen Martins was the inspiration and director behind it all. Through a study of Helen Martins' background and life, and their effects upon her psyche, a rigorous attempt has been made to reach some understanding of why she became a recluse, and what caused her to create this unique body of work comprising her entire domestic environment. She became increasingly asocial as her life progressed, and ultimately ended it by committing suicide in 1976. Through the universality of symbolism, the meanings of the subjects, themes and concerns which she chose to depict are studied. Then, together with some knowledge of her life and personal influences, an attempt has been made to deduce what it was that Helen Martins was trying to express and work through in her creations. This study also led to an awareness of the fact that, although each one is unique, there are many examples of Outsider Art throughout the world. Fundamentally, creators of Outsider Art remain asocial in relation to their cultural milieu and cultural context. Some other examples of Outsider Art, both in South Africa as well as in Europe and India, were visited, and are described and compared with The Owl House as well as with one another. The way in which society reacts or responds to Outsider Art and its creators is studied through the comprehensive records of one specific case which caused great controversy in Johannesburg during the 1970s. Ultimately, working alone or with assistance, it is the Outsider artist who is the driving force behind these unique works, and whose indefinable inner fire of passion alone makes it possible to bring them into being. It would seem that the fascination with Outsider Art is that through their work, creators allow others a glimpse into a different sense of reality which is both mysterious and inexplicable.
Keywords: Sculptors -- South Africa -- Biography; Martins, Helen Elizabeth, 1897-1976; Owl House (Nieu Bethesda, South Africa); Art brut; Women artists -- South Africa; Nieu bethesda (South africa) -- Description and travel; Primitivism in art; Creation (Literary, artistic, etc.); Artists -- Psychology; Symbolism in art